2013
DOI: 10.3899/jrheum.130528
|View full text |Cite
|
Sign up to set email alerts
|

Nailfold Capillaroscopy for Prediction of Novel Future Severe Organ Involvement in Systemic Sclerosis

Abstract: Capillaroscopy may be predictive of novel future severe organ involvement in SSc, as attested by 2 independent cohorts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
124
0
17

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 129 publications
(146 citation statements)
references
References 12 publications
5
124
0
17
Order By: Relevance
“…This may suggest that myocardial fibrosis may be related to CV follow-up of 18-24 months, the authors found a close relationship between worsening NVC grade, severe lung disease and peripheral vascular involvements. The same group confirmed these results in a larger and independent cohort 2 . In our study, we found a close relationship between NVC > grade 2 and the occurrence of CV events, strengthening the potential clinical value of NVC in CV risk stratification of SSc patients.…”
Section: Limitations Of the Studysupporting
confidence: 70%
See 2 more Smart Citations
“…This may suggest that myocardial fibrosis may be related to CV follow-up of 18-24 months, the authors found a close relationship between worsening NVC grade, severe lung disease and peripheral vascular involvements. The same group confirmed these results in a larger and independent cohort 2 . In our study, we found a close relationship between NVC > grade 2 and the occurrence of CV events, strengthening the potential clinical value of NVC in CV risk stratification of SSc patients.…”
Section: Limitations Of the Studysupporting
confidence: 70%
“…Its importance to predict systemic organ involvement and peripheral vascular disease 2,20 was recently studied. Smith al.…”
Section: Nvc Grade and CV Eventsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is the first to show an association between the number and size of CT with capillary loss and neoangiogenesis, 2 prominent features of the late NVC pattern, which is known to be the most severe, since the majority of SScrelated complications are observed in patients with this NVC pattern (14,15). In addition, the number and size of CT appear to be useful to identify a subgroup of patients at risk of severe SSc-related vasculopathy: patients with profuse CT more frequently exhibit digital ulcers, and patients with pseudotumoral CT also more commonly have precapillary PAH.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, some studies have shown that the late NVC pattern was predictive of the further development of severe peripheral vasculopathy and pulmonary vascular disease (14,20,21), and Sebastiani et al (22,23) showed that capillary loss, one of the main characteristics of the late NVC pattern, was the most relevant parameter to evaluate the risk of developing new digital ulcers of the capillaroscopic skin ulcer risk index formula.…”
Section: Discussionmentioning
confidence: 99%